YOUNG LEARNER’S ENGLISH SPEECH PRODUCTION - DEASY YUNITA SIREGAR (UIN Sumatera Utara, 2016)
The area of globalization makes a new competition in the life of all over the world. Those things which were not permitted to happen in the previous era, nowadays has been changed, everything might aware and people become more creative in fighting a competition. Due to the competition, People of Indonesia also prepare their selves and families to improve the human resources qualities. Parents do some efforts to improve their children capacity building such giving their children additional lessons in effort to prepare them to the era of competition. Therefore, nowadays English as an international language become important and young children are prepare to achieve it before entering school. Keywords: Language Acquisition, Behavioral Approach, Learning Theory, Young Learner’s Speech